2012
DOI: 10.1186/1756-9966-31-100
|View full text |Cite
|
Sign up to set email alerts
|

Array-based comparative genomic hybridization for genomic-wide screening of DNA copy number alterations in aggressive bone tumors

Abstract: BackgroundThe genetic pathways of aggressive changes of bone tumors are still poorly understood. It is very important to analyze DNA copy number alterations (DCNAs), to identify the molecular events in the step of progression to the aggressive change of bone tissue.MethodsGenome-wide array-based comparative genomic hybridization (array CGH) was used to investigate DCNAs of 14 samples from 13 aggressive bone tumors, such as giant cell tumors (GCTs) and osteosarcoma (OS), etc.ResultsPrimary aggressive bone tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
(22 reference statements)
1
17
0
Order By: Relevance
“…Spry2 protein is a good candidate to act as tumour suppressor in osteosarcoma. Corroborating with our data it is known that the q arm of chromosome 13 containing the SPRY2 gene frequently shows gene copy number losses in osteosarcoma [31,32]. Additionally it is shown that Spry2 expression interferes with ERK activation after FGF stimulation of osteoblasts [33].…”
Section: Discussionsupporting
confidence: 89%
“…Spry2 protein is a good candidate to act as tumour suppressor in osteosarcoma. Corroborating with our data it is known that the q arm of chromosome 13 containing the SPRY2 gene frequently shows gene copy number losses in osteosarcoma [31,32]. Additionally it is shown that Spry2 expression interferes with ERK activation after FGF stimulation of osteoblasts [33].…”
Section: Discussionsupporting
confidence: 89%
“…Oligo aCGH has been applied to several human tumors, revealing a high degree of heterogeneity within similar histotypes, and recurrent regions of copy-number abnormalities in the tumoral genomic DNA led to the discovery of genes that drive disease pathogenesis [7][9], [11].…”
Section: Discussionmentioning
confidence: 99%
“…Five OS cell lines (HOS, MOS, MG-63, NOS-1 and HuO 9N2) were used in this study. The MOS and NOS-1 cell lines were kindly provided by Dr Masahiko Kanamori (School of Medicine, University of Toyama, Toyama, Japan) (32)(33)(34)(35)(36). Three cell lines (HOS, MG-63, and HuO 9N2) were obtained from the Japanese Collection of Research Bioresources cell bank (Ibaraki, Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%